Female need for paternal care shapes variation in extra-pair paternity in a cooperative breeder. (11th January 2020) - Cousseau, Laurence; Van de Loock, Dries; Githiru, Mwangi; Vangestel, Carl; Lens, Luc
Abstract: Socially monogamous females regularly mate with males outside the pair bond. The prevailing explanation for this behavior is that females gain genetic benefits resulting from increased fitness of extra-pair offspring. Furthermore, because of the risk of reduced paternal care in response to cuckoldry, females are expected to seek extra-pair copulations when they can rear offspring with little help from their social partner ("constrained female" hypothesis). We tested these hypotheses and analyzed variation in paternal care in the Afrotropical, facultative cooperative breeding placid greenbul ( Phyllastrephus placidus ). Overall, approximately 50% of the offspring resulted from extra-pair (and extra-group) mating. Identified extra-pair males were in most cases neighboring dominant males, yet never within-group subordinates. As predicted by the constrained female hypothesis, the occurrence of extra-pair paternity (EPP) increased with the number of cooperative helpers (and not with total group size). However, dominant males did not adjust their food provisioning rates in response to EPP. Although extra-pair males were more strongly related to the dominant female and less heterozygous than the latter's social mate, this did not result in more inbred extra-pair offspring, likely because identified extra-pair males were not representative of the extra-pair male population. While earlier studies on EPP mainly focused on male genetic quality, results from this study provide evidence that female's social context may affect extra-pair strategies too. Abstract : In many bird species, females mate with males outside the pair bond. Because of the risk of reduced paternal care in response to cuckoldry, females are expected to seek extra-pair copulations when they can rear offspring with little help from their social partner. We showed in the cooperative breeding placid greenbul that extra-pair paternity increased with the number of helpers in accordance with the hypothesis that helpers liberate females from their dependency on paternal care.